First record of conura (Conura) maculata (fabricius, 1787) (hymenoptera, chalcididae) parasitizing opsiphanes invirae amplificatus stichel, 1904 (lepidoptera, nymphalidae) in the Province of Corrientes, Argentina - Gervazoni, Paula Belen (2018)
We report the first record of Conura (Conura) maculata (Fabricius, 1787) in the province of Corrientes, Argentina. A total of 85 adult wasps of C. maculata were obtained from 3 chrysalides of Opsiphanes invirae amplificatus Stichel, 1904, a lepidopteran pest of native and exotic palm trees. This is the first report of the occurrence of this parasitoid in the province of Corrientes, extending this species’ known distribution in the country. This is also the first report of the parasitoid-host interaction between these 2 species for Argentina.